Implementasi Model Pembelajaran Inkuiri dalam Meningkatkan Motivasi Belajar Murid Kelas V SD Miftahul Huda Plosokandang Kedungwaru Tulungagung - Abdul Rahman; Mohamad Sodik (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Finding out how the inquiry learning approach is applied to raise the learning motivation of Class V pupils at SD Miftahul Huda Plosokandang Kedungwaru Tulungagung, is the aim of the study. Qualitative research is the research methodology. Interviews, observations, and documentation were employed as data gathering methods. data reduction, data display, data analysis, and conclusion/verification. 1) The inquiry learning methodology is implemented for grade V students at SD Miftahul Huda Plosokandang Kedungwaru Tulungagung, following the proper procedures, which include doing observations before posing questions to both instructors and students. 2) A questionnaire that was given to the Class V pupils of SD Miftahul Huda Plosokandang Kedungwaru Tulungagung revealed that the students' learning motivation fell into the medium range. Furthermore, this statement receives an average score of 2.98 with a percentage of 74%, or in the High category, based on the mean or average value of student learning motivation.